Dow Chemical Company plant in Freeport, Texas - Dow Chemical Company (1952)
General exterior view, taken at night, of the Dow Chemical Company Texas Division plant located in Freeport, Texas. A range of products and processes were researched, developed, and produced at the plant, including chlorination, phenol, and magnesium.
Keywords: Industries; Dow Chemical Company